Empowering Social Work Leveraging SNA Tools for Cyber Threat Detection in social media to Enhance Digital Well-Being - Berzinji, Ala Berzinji (Sulaimani Journal for Humanities, 2026)
In the ever-evolving digital landscape characterized by the proliferation of cyber threats on social media platforms, this research investigates the strategic application of Social Network Analysis (SNA) tools to bolster the capabilities of social workers in preserving digital well-being. The study introduces a sophisticated framework that leverages SNA tools for identifying, monitoring, and analysing cyber threat nodes within social media networks. By proficiently identifying individuals or entities engaged in malicious activities like cyberbullying and harassment, social workers can effectively mitigate digital threats. The framework incorporates real-time monitoring, utilizing SNA metrics and algorithms to detect patterns indicative of malicious behaviour, enabling prompt interventions and support for affected individuals. Emphasizing continuous analysis of social media posts related to cyber threats, the research equips social workers to scrutinize content, trends, and dynamics surrounding cyber threat nodes, enhancing their understanding of the digital landscape. The study aims to empower social workers with a systematic approach to navigate social media's complexities and proactively address digital threats. Envisioning proactive measures against cyber threats, the outcomes aim to cultivate improved digital well-being. This research holds implications for developing innovative strategies and tools aligned with the evolving nature of cyber threats, ensuring that social workers maintain a leading role in safeguarding the digital welfare of individuals and communities
Keywords: Cyber Threat Detection; Cyberbullying; Social Network Analysis; Online Communities; Digital WellBeing